The spatiotemporal characteristics and obstacle factors of the coupled and coordinated development of agricultural and rural digitalization and food system sustainability in China - Li, Ye; Chen, Yiyan (Frontiers in Sustainable Food Systems, 2024)
Introduction The sustainable development of China’s food system is an essential requirement for realizing the digital transformation of agriculture and rural areas and the main target for the big release of agricultural and rural digitalization dividends and the scale of feedback. What are the current trends of change in China’s agricultural and rural digitization and sustainable development of the food system? Have they achieved a high level of coordinated development? What are the factors constraining their coordinated development? Methods This work is based on 30 Chinese provincial administrative areas from 2011 to 2020. We adopt the entropy weight method to calculate the comprehensive development index of the agricultural and rural digitization and food system sustainability, respectively. The coupling degree and coupling coordination degree of the two systems are calculated by applying the coupling coordination degree model. The obstacle degree model was used to diagnose the obstacles constraining the coupling and coordinated development of the coupled systems. Results This study found that the development index of China’s provincial agricultural and rural digitization and food system sustainability increased gradually from 2011 to 2020. The coupling of the two systems is mainly in the high-level coupling stage, but the coupling coordination degree is primarily in the low and medium coupling coordination intervals. These results are heterogeneous across China’s four geographic regions: east, center, west, and northeast. The level of rural digital platform construction and rural digital industrialization is the most essential indicator-level and element-level barriers to agricultural and rural digitalization, respectively. Per capita food possession and food stability are, respectively, the most critical indicator-level and element-level barriers to the food system sustainability. Discussion The research in this work contributes to a comprehensive understanding of the evolutionary trends in agriculture and rural digitalization and the food system sustainability in the country as a whole and within the country. Although the two systems have not achieved a high level of coordinated development, the coupling degree and coupled coordination degree show a positive feedback relationship. The analysis of the obstacle factors helps to recognize the main bottlenecks constraining the coupled and coordinated development of the systems at a more specific level.